Combined Effects of Parenting in Childhood and Resilience on Work Stress in Nonclinical Adult Workers From the Community - Sameshima, Hiroto; Shimura, Akiyoshi; Ono, Kotaro; Masuya, Jiro; Ichiki, Masahiko; Nakajima, Satomi; Odagiri, Yuko; Inoue, Shigeru; Inoue, Takeshi (Frontiers in Psychiatry, 2020)
Background: Stress responses induced by job stressors are modified by individual factors. Perceived parental bonding and resilience would play important roles as such individual factors. In this study, we analyzed the mediating roles of resilience on parenting, job stressors, and stress responses among adult workers from the community. Methods: A total of 528 workers participated in this study after providing written consent, and completed questionnaires on demographic data, as well as Parental Bonding Instrument, Connor-Davidson Resilience Scale, and Brief Job Stress Questionnaire. Associations between perceived parental bonding, resilience, perceived job stressors, and the psychological and physical stress response (PPSR) were analyzed using structural equation modeling. Results: Structural equation modeling with covariance structure analysis showed that parental overprotection reduced resilience and increased perceived job stressors and PPSR. Resilience and perceived job stressors and their combination mediated the effect of parental overprotection on PPSR. Resilience mediated the effect of parental overprotection on perceived job stressors. Perceived job stressors mediated the effect of resilience on PPSR. Parental care had opposite effects to parental overprotection, but the difference was small. Conclusion: In this study, we showed that perceived parental bonding affects resilience, and that both factors affect the stress response and perceived job stressors. These findings suggest that parental bonding and resilience are major individual factors affecting work stress, and should be noted when considering industrial hygiene measures for individual workers.